Meeting report: 3rd Neuroblastoma Research Symposium, Liverpool, 6–7th November, 2013. Issue 9 (7th May 2014) - Bell, Emma; Chen, Lindi; Viprey, Virginie F.; Blanchard, Guy B.
<x xml:space="preserve">Abstract</x> Neuroblastoma is an embryonal malignancy of the developing neural crest. Despite improvements in treatment, prognoses remain dire for patients with high‐risk disease. Interest in this enigmatic cancer has led to a rapidly changing research landscape and we report on the recent advances in four themes that were discussed at the 3rd Neuroblastoma Research Symposium: (1) The epigenetic signature of neuroblastoma and the epigenetic control of tumour development, (2) novel approaches to targeting MYCN, (3) valuable in vivo modelling and (4) improving differentiation therapies based on a knowledge of normal sympathetic neuron development. Through lively discussion, the development of combined therapies with synergistic effects for which we have a good mechanistic understanding emerged as offering greatest promise. Drug synergies enhance efficacy but also specificity, the latter crucial for reducing long‐term side effects in young children. Pediatr Blood Cancer 2014;61:1711–1713. © 2014 Wiley Periodicals, Inc.